Description of Cornigamasus allotritosternus sp. nov. (Mesostigmata: Parasitidae) from China, with an emphasis on the ontogenetic development of setae - Yao, Mao-Yuan; Guo, Jian-Jun; Yi, Tian-Ci; Jin, Dao-Chao (Zootaxa, 2020)
A new species, Cornigamasus allotritosternus sp. nov., is described based on the larva, protonymph, deutonymph and adult female and male collected from cow dung in Guizhou Province, China. The ontogenetic development of the gnathotectum, dorsal shields, ventral shields, and the chaetotaxy of the gnathosoma, idiosoma and legs are discussed and illustrated.